2021
DOI: 10.3390/molecules26237376
|View full text |Cite
|
Sign up to set email alerts
|

A Review of HER4 (ErbB4) Kinase, Its Impact on Cancer, and Its Inhibitors

Abstract: HER4 is a receptor tyrosine kinase that is required for the evolution of normal body systems such as cardiovascular, nervous, and endocrine systems, especially the mammary glands. It is activated through ligand binding and activates MAPKs and PI3K/AKT pathways. HER4 is commonly expressed in many human tissues, both adult and fetal. It is important to understand the role of HER4 in the treatment of many disorders. Many studies were also conducted on the role of HER4 in tumors and its tumor suppressor function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 142 publications
2
25
0
Order By: Relevance
“…Generally, cancer has been linked to mutations in the ERBB4 gene [ 25 ], which in this study was confirmed as a highly unstable gene. No information was found on the sequenced P.Q264* missense mutation in this gene, even if this has been already sequenced in a colon cancer cell line [ 26 ].…”
Section: Discussionsupporting
confidence: 64%
“…Generally, cancer has been linked to mutations in the ERBB4 gene [ 25 ], which in this study was confirmed as a highly unstable gene. No information was found on the sequenced P.Q264* missense mutation in this gene, even if this has been already sequenced in a colon cancer cell line [ 26 ].…”
Section: Discussionsupporting
confidence: 64%
“…The pathway analysis results suggest that MAPK and NOTCH1 are involved in cancer progression at evolving state, followed by enriched PI3K/AKT, ERBB4 and MET pathways at maintaining and adaptive states. This implies that patients stratified by the evolutionary state at the time of diagnosis could benefit from the drugs targeting these pathways, many of which were already approved or being investigated in clinical trials (Bonello et al, 2018; Diaz-Padilla et al, 2015; El-Gamal et al, 2021; Konstantinopoulos et al, 2021; Vergote et al, 2020). Importantly, MAPK, PI3K/AKT and ERBB4 pathways remain unaffected by platinum-taxane chemotherapy and are active also in relapses.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-seq in CC-PDX and primary tumors showed several mutations, including those in genes encoding FLT3, ERBB4, CDKN2A, Kinase Insert Domain Receptor (KDR), fibroblast growth factor recep-tor 2 (FGFR2), enhancer of zeste homolog 2 (EZH2), SMAD Family Member 4 (SMAD4), ataxia telangiectasia mu-tated (ATM), SWI/SNF Related, Matrix Associated, Actin Dependent Regulator Of Chromatin, Subfamily B, Member 1 (SMARCB1), Serine/threonine kinase 11 (STK11), and RB1. ERBB4 is a member of the EGFR family, comprising four transmembrane tyrosine kinases [ 43 ]. FGFR2 belongs to the FGFR family [ 44 ].…”
Section: Discussionmentioning
confidence: 99%